Perancangan dan Implementasi Augmented Reality Pemantauan Titik Reklame Kota Semarang Menggunakan QR-Code Berbasis ANDROID - Aji Prajayudha Permana; Oky Dwi Nurhayati; Kurniawan Teguh Martono (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2016)
Nowadays, information technology is needed, in all aspects of life almost inseparable with information technology. Information technology was venturing into the world of work and business that aims to improve, simplify and save business. This strategy was used in advertisement by using Augmented Reality technology that are used to compare the object of the marker and the original advertisement Application of Augmented Reality technology that is used to verify a billboard built by MDLC (Multimedia Development Life Cycle) method consists of making the concept, design, gather materials, manufacturing, inspection, and measures distribution. Inspection measures using the Black-Box Testing method comprising Application Function tests, test lighting intensity, and distance of the camera from the marker. Based on the examination and analysis of the results to the application that is built, it can be concluded that the use of the application can be a means to assist in the verification process with a series of billboards and distance testing lighting intensity during morning and afternoon .